Clinical Study of Limosilactobacillus reuteri for the Treatment of Children with Chronic Tic Disorders/Tourette Syndrome: A Mid-Term Efficacy Evaluation - Yan Liang; Lin Wan; Guanglei Wang; Huimin Yan; Jing Zhang; Xinting Liu; Ziyan Zhang; Gang Zhu; Guang Yang (Neurology and Therapy)
Abstract Introduction Gut microbiota plays an important role in tic disorders (TDs); however, clinical research on probiotics for chronic TDs treatment is lacking. We aimed to investigate the effectiveness of probiotics, hypothesizing that their clinical efficacy is comparable to that of clonidine in treating chronic TDs. Methods Patients were randomly assigned to receive either Limosilactobacillus reuteri or clonidine transdermal patch treatment for 8 weeks while maintaining their existing treatment. The Yale Global Tic Severity Scale (YGTSS); Swanson, Nolan, and Pelham-IV Scale (SNAP-IV); and Child Behavior Check List (CBCL) scores were assessed before and after treatment. Results We matched the patients in both groups for age, sex, age at onset, and tic type. A significant improvement in YGTSS scores was observed in both groups (p = 0.024). The improvement in attention deficits on the SNAP-IV scale was similar between the two groups, with no significant difference (p = 0.465). For hyperactivity disorder, after matching patients in both groups for age, sex, age at onset, tic type, and Children’s Yale-Brown Obsessive Compulsive Scale (CY-BOCS) scores, a significant difference in improvement was observed between the groups (p = 0.010), with the probiotics group showing greater improvement (0.3 ± 0.58 vs. 0.1 ± 0.50). At 9 weeks, social ability on the CBCL scale increased by 3.2 ± 6.26 from baseline in the probiotics group and by 0.6 ± 4.07 in the clonidine group, with a significant difference between the two (p = 0.049). Although there was no significant difference in behavioral problems between the two groups (p = 0.347), the trend of improvement was more pronounced in the probiotics group than in the clonidine group (12.7 ± 25.86 vs. 8.4 ± 13.15). Conclusion The mid-term efficacy evaluation demonstrated that L. reuteri, when added to the treatment of children with chronic TDs, was more effective in improving tic symptoms than clonidine transdermal patch treatment. Additionally, it provided moderate improvement in hyperactivity symptoms. Trial Registration chictr.org.cn (registration numbers ChiCTR2200056708, ChiCTR2200056578).